The political work of Northern women writers and the Civil War, 1850-1872 - Sizer, Lyde Cullen (Civil War America., 2000)
This study explores the lives of nine Northern American female writers of the Civil War period. It examines how, through their writing, they engaged in the national debates of the time. The author shows how they and others used their writing to make sense of topics like war, womanhood and slavery.